Human Development index and Informatisation of Society in CIS - Rodionova, Irina; Gordeeva, Anastasia (Bulletin of Geography. Socio-economic Series, 2010)
Knowledge and know-how of calculation methods of indicators and indices allow to evaluate, compare and correlate if not fully then to a considerable extent the situation in different countries and regions of the world. Moreover, in countries with "transitional economy" to which Russia and other countries of former Soviet Union are attributed to, the situation has significantly changed and it is necessary to adjust the directions and perspectives of development considering the changed environment. The article characterizes a position of Russia and other CIS’s countries (Commonwealth of Independent States) on the international rating of Human Development Index and Networked Readiness Index.